The manner of contention: Pluralism at Gezi - Ors, Ilay Romain; Turan, Omer (Sage Publications Inc, 2015)
This article is based on an ethnographic investigation of the Gezi Park events in 2013. Starting from the much acknowledged characteristics of Gezi as being its cultural and political pluralism and its commitment to non-violence, in this article we are engaging with two interlinked questions: How has the plurality of participants and orientations been possible to attain, and how could this pluralism be contained without any major conflict at Gezi? We propose to provide an answer by focusing on the manners of everyday life at Gezi Park during the time of dissidence, which we conceptualize as manner of contention'. It was the manner of contention that characterized the specific ways in which contentious politics took place at Gezi and prevented the formation of clashes among the plurality of contenders. The ethnographic research delineates at least 4 components of manner of contention in the case of Gezi: an ethos of collective work; a spirit of exchange and gift-giving; politeness; and non-violence.
Keywords: Gezi Park; Stanbul; Manner Of Contention; Pluralism; Protest; Park